2023
DOI: 10.1186/s13007-023-01008-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of protoporphyrin IX and magnesium protoporphyrin IX in Arabidopsis thaliana and Camellia sinensis using UPLC-MS/MS

Abstract: Backgrounds Insertion of Mg2+ into protoporphyrin IX (PPIX) to produce magnesium-protoporphyrin IX (Mg-PPIX) was the first step toward chlorophyll biosynthesis, which not only imparts plants green pigmentation but underpins photosynthesis. Plants that blocked the conversion of PPIX to Mg-PPIX displayed yellowish or albino-lethal phenotypes. However, the lack of systematic study of the detection method and the metabolic difference between species have caused the research on chloroplast retrograd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In addition, the lipid compositions of the inner and outer cotyledons differed significantly [133]. To analyze the lipid composition of tea tree (Camellia sinensis) seed oil and to reveal the functional properties of different lipid components, ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS)-based lipidomics was used to characterize the lipid profile; this showed that seed oil has a more diverse range of glycerides in tea tree seeds, with a relatively higher content of glycerol diesters, compared to other plant oils [134].…”
Section: Lipidomics For Oil Structure and Quality Identificationmentioning
confidence: 99%
“…In addition, the lipid compositions of the inner and outer cotyledons differed significantly [133]. To analyze the lipid composition of tea tree (Camellia sinensis) seed oil and to reveal the functional properties of different lipid components, ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS)-based lipidomics was used to characterize the lipid profile; this showed that seed oil has a more diverse range of glycerides in tea tree seeds, with a relatively higher content of glycerol diesters, compared to other plant oils [134].…”
Section: Lipidomics For Oil Structure and Quality Identificationmentioning
confidence: 99%